If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 13 = 4x + 7 Reorder the terms: 13 + 12x = 4x + 7 Reorder the terms: 13 + 12x = 7 + 4x Solving 13 + 12x = 7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 13 + 12x + -4x = 7 + 4x + -4x Combine like terms: 12x + -4x = 8x 13 + 8x = 7 + 4x + -4x Combine like terms: 4x + -4x = 0 13 + 8x = 7 + 0 13 + 8x = 7 Add '-13' to each side of the equation. 13 + -13 + 8x = 7 + -13 Combine like terms: 13 + -13 = 0 0 + 8x = 7 + -13 8x = 7 + -13 Combine like terms: 7 + -13 = -6 8x = -6 Divide each side by '8'. x = -0.75 Simplifying x = -0.75
| 2(4x+1)=90 | | 6+-6x=5x+61 | | N-25=18 | | 2(3x-1)-6x=-4 | | 3x+4x+5=-3 | | N-25= | | 3(7x+7)=252 | | (W+1)(2w-3)=5 | | 5=3k-2k | | Log(x)=9 | | 3x+4x+5=3 | | D+4.7=2.8t(7.4) | | 6(7m+3)= | | 3x+4x-5=3 | | -0.2x(-0.07)= | | 9b=4b-25 | | 7x+1=8x+16 | | 1650-25h=1325 | | 6x-3x=-6+5x | | 5(x-7+4)=34 | | -20x-8+7=-5 | | .23=log(x) | | 3x-4x-5=3 | | y-7=(x+4) | | 2(x+4)+2(x)=4(x+2) | | 3x-4x+5=-3 | | 3b=10-b | | 5(3x+7)=35 | | 3*-5+12-5*-5=22 | | -12=-15x | | 3x+4x-5=-3 | | 7x+5=44-6x |